2020
DOI: 10.1177/0020731420983749
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Government Policies in Controlling COVID-19 in India

Abstract: The purpose of this study is to find the demographic factors associated with the spread of COVID-19 and to suggest a measure for identifying the effectiveness of government policies in controlling COVID-19. The study hypothesizes that the cumulative number of confirmed COVID-19 patients depends on the urban population, rural population, number of persons older than 50, population density, and poverty rate. A log-linear model is used to test the stated hypothesis, with the cumulative number of confirmed COVID-1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…En un estudio similar de contagio de COVID-19 que fue elaborado por una regresión múltiple por el método de mínimos cuadrados ordinarios se presentó un coeficiente de 0.25 para la tasa de pobreza, sin embargo, el estudio no fue realizado por género, en tanto que en esta investigación se tiene un coeficiente de 4.98 para el contagio en mujeres en situación de pobreza extrema y de carencias sociales se tiene 1.23 y 2.49 para hombres y mujeres respectivamente. Se mencionó carencias sociales, debido a que esta variable representa los indicadores de pobreza, de tal forma que se aprecia que las mujeres con mayores carencias en las comunidades rurales son las de mayor riesgo de contagio por COVID-19 (Pandey, & Saxena, 2020).…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…En un estudio similar de contagio de COVID-19 que fue elaborado por una regresión múltiple por el método de mínimos cuadrados ordinarios se presentó un coeficiente de 0.25 para la tasa de pobreza, sin embargo, el estudio no fue realizado por género, en tanto que en esta investigación se tiene un coeficiente de 4.98 para el contagio en mujeres en situación de pobreza extrema y de carencias sociales se tiene 1.23 y 2.49 para hombres y mujeres respectivamente. Se mencionó carencias sociales, debido a que esta variable representa los indicadores de pobreza, de tal forma que se aprecia que las mujeres con mayores carencias en las comunidades rurales son las de mayor riesgo de contagio por COVID-19 (Pandey, & Saxena, 2020).…”
Section: Resultados Y Discusiónunclassified
“…En la India se realizó un estudio y se encontró que el número acumulado de pacientes con COVID-19 confirmados, depende de la población urbana, la población rural, el número de personas mayores de 50 años, la densidad de población y la tasa de pobreza, pues se encontró a través de un modelo por mínimos cuadrados ordinarios que el contagio de Covid-19 presentó un coeficiente de 0.25 para la tasa de pobreza, así como un coeficiente de 1.61 y de -0.33 para zonas urbanas y rurales respectivamente, y para la edad presentó un coeficiente de -0.03 (Pandey & Saxena, 2020).…”
Section: Importancia Del Covid-19 En La Poblaciónunclassified
“…In some LMIC countries with large rural populations, national policies identified through the review appeared not to differentiate between rural and urban areas [17,18]. Examples of challenges were described in reviews of India's national policies in which authors identified overall health policy and system inadequacies that could hinder an effective COVID-19 response, but also highlighted the capacity for successful responses in states with large rural populations such as Uttar Pradesh and Rajasthan [19,20].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…There are two theoretical assumptions which are usually mentioned in most articles: age structure of society and population density. The former frequently refers to elderly citizens who belong to the high-risk group and are more vulnerable to the severe symptoms and illnesses related to or provoked by the coronavirus 24 . The latter is more selfexplanatory and refers to the social distance, a guarantee of which could be hindered by the high density of population, leading to an increased number of infections and deaths 25 .…”
Section: Socio-demographic Factorsmentioning
confidence: 99%